Maintaining and Sharing a Haudenosaunee Identity: Onondaga Collective Memory and Social Media. Issue 2 (3rd April 2018) - Modrow, Sebastian
ABSTRACT: In this article, I survey the Onondaga Nation's social media outlets in the light of collective memory theory. The article identifies several core topics of the nation's identity narratives which, all together, are perceived as an expression of Onondaga functional memory. The role of wampum belts as medial cues to that memory is highlighted as well as the role of social media in the struggle against the negative effects of native media invisibility.